DESIGN AND ANALYSIS OF DUAL BAND H SHAPED RECTANGULAR MICROSTRIP PATCH ANTENNA - Mansoori, SaimaTabassum; Koshta, Rahul (International Journal of Research -GRANTHAALAYAH, 2017)
In this paper we are study about wireless antenna, which are used for wireless communication, the wireless communication system are having important role in service requirement. We are design and analyzed the Dual Band type H Shaped Rectangular Microstrip Patch Antenna and S- parameters are finding out using of various Substrate height (H).